2021
DOI: 10.1002/solr.202100501
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Bi2S3/TiO2/MoS2 S‐Scheme Heterostructure with a Switchable Charge Migration Pathway for Selective CO2 Reduction

Abstract: Switching between the redox potential of an appropriate semiconductor heterostructure could show critical applications in selective CO2 reduction. Designing a semiconductor photocatalyst with a wavelength‐dependent response is an effective strategy for regulating the direction of electron flow and tuning the redox potential. Herein, the switching mechanism between two charge migration pathways and redox potentials in a Bi2S3/TiO2/MoS2 heterostructure by regulating the light wavelength is achieved. In situ irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 75 publications
(138 reference statements)
0
22
0
Order By: Relevance
“…As reported previously, the absolute electronegativity (x) values of the TiO 2 and MoO 3 photocatalysts were 5.81 and 6.4 eV, respectively. 56,58 From the above results, the band gap values of the synthesized TiO 2 and MoO 3 photocatalysts were found to be 3.1 and 2.82 eV, respectively. Hence, from eqn (3) and ( 4), the E CB and E VB values were calculated and found to be (À0.24 and 0.49 eV) and (2.86 and 3.31 eV) for the synthesized TiO 2 and MoO 3 photocatalysts, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As reported previously, the absolute electronegativity (x) values of the TiO 2 and MoO 3 photocatalysts were 5.81 and 6.4 eV, respectively. 56,58 From the above results, the band gap values of the synthesized TiO 2 and MoO 3 photocatalysts were found to be 3.1 and 2.82 eV, respectively. Hence, from eqn (3) and ( 4), the E CB and E VB values were calculated and found to be (À0.24 and 0.49 eV) and (2.86 and 3.31 eV) for the synthesized TiO 2 and MoO 3 photocatalysts, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…The results are consistent with other studies. 56,58 Based on the optical study, the band gap values of TiO 2 and TO-MO-30 were found to be 3.1 and 2.9 eV, respectively, indicating that the visible light absorption of TiO 2 is significantly enhanced. The formation of the heterostructure would be the reason for the enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The generated ˙OH was detected by using DMPO as a radical trapping substance in an aqueous solution. 8…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…5 Consequently, the efficiency of charge kinetics operations is greatly reduced, and the photocatalytic activity is significantly decreased. Several techniques have been studied to enhance the photocatalytic efficiency of semiconductor nanostructures like defect engineering, doping of metals or non-metals, construction of heterojunctions, metal loading, etc., [6][7][8] Engineering defects in semiconductor photocatalysts is an efficient method to control and change the regional coordination of active sites in semiconductor photocatalysts. 9 For altering the bandgap energies in nanostructures and improving photoexcited electron transport, defect engineering offers great potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation